Lolita [videorecording (DVD)] - Kubrick, Stanley; Mason, James, 1909-1984; Winters, Shelley; Lyon, Sue, 1946-2019-; Sellers, Peter, 1925-1980; Nabokov, Vladimir Vladimirovich, 1899-1977 (Metro-Goldwyn-Mayer ; Distributed by Warner Home Video, 2007)
Stanley Kubrick's sixth film is a brilliant, sly adaptation of Vladimir Nabokov's celebrated yet infamous 1955 novel. It chronicles a middle-aged literature professor's unusual and doomed sexual passion/obsession for a seductively precocious pubescent "nymphet" named Lolita. Thanks to the film industry's production code, the film is mostly suggestive, with numerous double entendres and metaphoric sexual situations, while the story has been transformed into a black comedy and murder mystery. The film lacks the element that enabled most readers to understand the novel--Humbert Humbert's exquisite inner voice. As a consequence the film is big, luxurious, and full of a barren, cold humor, yet a visual tour-de-force in elegant black-and-white.